1989
DOI: 10.1042/bj2580755
|View full text |Cite
|
Sign up to set email alerts
|

Identification of signalling and non-signalling binding contributions to enzyme reactivity. Alternative combinations of binding interactions provide for change in transition-state geometry in reactions of papain

Abstract: 1. 2-(N'-Acetyl-L-phenylalanyl)hydroxyethyl 2'-pyridyl disulphide (compound V) was synthesized, and a study of the pH-dependence of the second-order rate constant (k) for its reaction with the catalytic-site thiol group of papain (EC 3.4.22.2) was used to evaluate the consequences for transition-state geometry of the presence of a hydrophobic occupant for the S2 subsite of the enzyme in the absence of the N-H component of the P1-P2 amide bond. 2. Comparison of the pH-dependences of K for reactions of compound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Transition-state geometry is the fundamental characteristic on which catalytic ability depends, and the reactivity of a catalytic-site nucleophile that plays a central role in the catalytic act is a prime target for investigation of factors that contribute to the control of transition-state geometry. The cysteine proteinase papain (EC 3.4.22.2) provides valuable opportunities for the study of the interdependence of binding interactions with each other and with catalytic-site chemistry (Kowlessur et al, 1989b). The reactivity of its catalytic site responds to combinations of hydrogenbonding and hydrophobic effects in its extended binding site (Brocklehurst et al, 1987a(Brocklehurst et al, , 1988aKowlessur et al, 1989a Kowlessur et al, ,b, 1990Templeton et al, 1990;Berti et al, 1991;Hanzlik et al, 1991;Patel et al, 1992).…”
mentioning
confidence: 99%
“…Transition-state geometry is the fundamental characteristic on which catalytic ability depends, and the reactivity of a catalytic-site nucleophile that plays a central role in the catalytic act is a prime target for investigation of factors that contribute to the control of transition-state geometry. The cysteine proteinase papain (EC 3.4.22.2) provides valuable opportunities for the study of the interdependence of binding interactions with each other and with catalytic-site chemistry (Kowlessur et al, 1989b). The reactivity of its catalytic site responds to combinations of hydrogenbonding and hydrophobic effects in its extended binding site (Brocklehurst et al, 1987a(Brocklehurst et al, , 1988aKowlessur et al, 1989a Kowlessur et al, ,b, 1990Templeton et al, 1990;Berti et al, 1991;Hanzlik et al, 1991;Patel et al, 1992).…”
mentioning
confidence: 99%
“…There is considerable variation among members of the papain family, however, in substrate specificity and catalytic-site reactivity [81,[153][154][155][156][157][158], which reveals that this view is correct only for low-resolution aspects of the mechanism, such as the roles of the cysteine and histidine components of the catalytic-site ion pair. The results of detailed mechanistic investigations on papain and some of its natural variants (discussed in [44,45]) have revealed that papain exhibits characteristics at one end of a spectrum of chemical behavior with actinidin at the other, and with caricain and ficin occupying intermediate positions.…”
Section: Cysteine Proteinasesmentioning
confidence: 99%
“…Clear evidence for this phenomenon [141,[155][156][157] is provided by the nature of the pH-k profiles for reactions of papain with substrate-derived 2-pyridyl disulfides used as thiol-specific, two-protonic-state reactivity probes [41]. These probes contain in one part of the molecule various potential binding sites and, in the other, the 2-mercaptopyridine leaving group to serve as a detector of the relative disposition of the thiolate and imidazolium components of the Cys25/His159 ion pair.…”
Section: Cysteine Proteinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the least well understood aspects of enzyme catalysis and active-centre chemistry is the range and nature of the kinetic consequences of electrostatic effects initiated by ionizations at various distances from and orientations to the catalytic site [6][7][8][9] ; evidence continues to accumulate that electrostatic effects [10] are a major factor in determining the behaviour of cysteine proteinases [4,[11][12][13][14][15][16][17][18][19][20][21][22]. The carboxy group of Asp"&) is the ionizable group nearest to the catalytic sites in both enzymes obeing separated from the (Cys#&)-S − \(His"&*)-Im + H (in which Im represents imidazole) ion pairs by approx.…”
Section: Introductionmentioning
confidence: 99%